A Case of Chyloperitoneum Secondary to Follicular Lymphoma and a Review of Prognostic Implications. (26th June 2016) - Jagosky, Megan; Taylor, Brice; Taylor, Stephanie Parks
Abstract : Chyloperitoneum, or chylous ascites, is a rare condition characterized by milky-appearing fluid with elevated triglyceride content and the presence of chylomicrons. Malignancy, specifically lymphoma, is reported to be the predominant cause in Western countries. Previously, the prognosis for patients with chyloperitoneum due to lymphoma has been reported as poor. We present a case of chyloperitoneum and chylothorax due to follicular lymphoma with excellent response to bendamustine and Rituxan. A review of the literature indicates that patients with chyloperitoneum associated with lymphoma generally have a favorable response to contemporary treatment regimens.